STUDENT TEACHER PREPAREDNESS FOR TEACHING PRACTICE AT FACULTY OF AGRICULTURE AND CONSUMER SCIENCES IN THE UNIVERSITY OF ESWATINI - Tsikati, Alfred Fana; Nsingwane, Sifiso (Advances in Social Sciences Research Journal, 2019)
Student preparation in teacher education is a crucial factor for teaching practice. Unfortunately, research conducted on student teacher preparedness for teaching practice at the Faculty of Agriculture and Consumer Sciences lacking. Thus, the purpose of the study wasto describe student teacher preparedness for teaching practice at the Faculty of Agriculture and Consumer Sciences at the University of Eswatini. This was a correlational study employing self-administered questionnaires in data collection. A census of 80 fourth year Agricultural Education and Consumer Sciences Education students was used. Post hoc inter-item reliability using Cronbach’s Alpha revealed that the questionnaire was .74 reliable. Three experts from the Department of Agricultural Education and Extension validated the instrument. Data were analyzed using descriptive and correlational statistics. Results revealed that student teachers were prepared for teaching practice on the following: student discipline; setting test and exam questions, student assessment practices; effective use of teaching aids; classroom management; understanding student behaviour; and Information and Communication Technology.The study concluded that the student teachers were prepared for teaching practice and there was congruence between the preparation and the teaching practice. The Faculty of Agriculture and Consumer Sciences should match the needs of students and those of the teaching practice school.